Research on the uncontrolled zero-sequence current of an open-end winding PMSM with common DC link - Hunter, Nick (2021)
This thesis describes the research based on a particular type of the motor drives called an open-end winding permanent magnet synchronous motor drive with common DC link. These types of drives are an arrangement of two three phase inverters connected to both ends of a permanent magnet synchronous motor and are fed from a single direct current source. Therefore, it has a return path between the two inverters. This allows the most prominent third harmonic back EMF to introduce the zero-sequence current. Hence, these kinds of motor drives suffer from the circulating zero-sequence current. Although this current usually is undesired and, therefore, suppressed using various control techniques, there are some cases when the suppression of this current is unfeasible. Hence, the zero-sequence current could be left flowing in the system. High-speed drives could be considered to be an example of such a system. The research introduced in this thesis is centred on the analysis of the mentioned zero-sequence current that is flowing in the system due to the specific properties of the machine. It features a full mathematical derivation of the nature of the zero-sequence current flowing in the system because of the machine side of the drive and a comprehensive analysis of the power loss in conductor due to this zero-sequence component. The analysis performed in this thesis resulted in a proposal of a couple of novel solutions for the mitigation of the zero-sequence component’s impact on the drive such as the torque ripple and the power loss in conductor. In addition, one of the research outcomes was the development of a novel technique that turns the disadvantage of having the zero-sequence component flowing freely in the drive to its advantage. In addition, the research produced in this thesis led to the development of a software solution that is meant to aid design and control engineers to mitigate the power losses in an open-end winding permanent magnet synchronous motor drive with common DC link.